EARLY DETECTION OF CHILDREN'S DEVELOPMENT ON STUNTING TODDLERS: Qualitative Study - Kartinawati, Komang Triyani; Pradnyawati, Luh Gede; Dwipayana, I Made Eka (JURNAL KEDOKTERAN, 2022)
Stunting is an impaired growth in children because of long-term insufficient nutrition from conception until the age of two. Regarding Basic Health Research 2018, the prevalence of stunting in Indonesia was 30.8%, higher than the WHO’s target. As stated in the Nutritional Status Monitoring, the prevalence of stunting in Karangasem from 2015 to 2017 was 27.5%, 26.1%, and 23.6% respectively. Early detection of child development status could be utilized as a pilot project to construct an intervention scheme for stunting prevention. This research aims for in-depth learning on the children growth status of stunting toddlers in the village of Ban, including gross motor, fine motor, language and adaptive skills. The research method was a qualitative design with a phenomenological approach. The in-depth interview was arranged with 15 participants sorted by purposive sampling, including 5 stunting toddlers, 5 mothers or babysitters of those toddlers, and 5 health personnel in the field. This result showed impairment of child development in long-term stunting toddlers. Without stimulation from parents, babysitters, and the social environment for those impaired children, they would undergo prolonged developmental failure. The data also showed that the majority of children experienced impairment in fine motor-adaptive skills whereas the gross motor and language skills were still normal. Keywords: Stunting; Nutrition; Child Development; In-depth Interview.